The Relationship Between Family Support and Patient Compliance in the Management of Diabetic Wounds at Griya Luka Pringsewu - Esa Artamevia; Hana Zumaedza Ulfa; Eko Wardoyo; Hardono (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: Diabetes mellitus is a chronic disease that often leads to diabetic wounds requiring continuous and proper care. Patient adherence to wound care remains a challenge and may be influenced by family support. This study aimed to determine the relationship between family support and patient adherence in diabetic wound care. Method: This study employed a quantitative correlational design with a cross-sectional approach. The population consisted of 60 patients with diabetic wounds, and 30 respondents were selected using quota sampling. Data were collected using family support and wound care adherence questionnaires. Data analysis was conducted using the Gamma test. Result: The results showed a significant relationship between family support and patient adherence in diabetic wound care, with a p-value of 0.043 and a correlation coefficient of 0.609, indicating a strong positive relationship. Most respondents had a moderate level of adherence. Conclusion: Family support is significantly associated with patient adherence in diabetic wound care, and strong family support can improve patient adherence in performing wound care.